Anti-Biofilm Activity of Laurel Essential Oil against Vibrio parahaemolyticus - Wenxiu Zhu; Jiaxiu Liu; Yue Zou; Shugang Li; Dongyun Zhao; Haisong Wang; Xiaodong Xia (Foods, 2023)
Vibrio parahaemolyticus is a primary seafood-associated pathogen that could cause gastroenteritis. It can attach to various surfaces and form a biofilm, which poses serious threats to food safety. Hence, an effective strategy is urgently needed to control the biofilm formation of V. parahaemolyticus. Laurel essential oil (LEO) is used in food, pharmaceutical and other industries, and is commonly used as a flavoring agent and valuable spice in food industries. The potential antibiofilm effects of LEO against V. parahaemolyticus were examined in this study. LEO obviously reduced biofilm biomass at subinhibitory concentrations (SICs). It decreased the metabolic activity and viability of biofilm cells. Microscopic images and Raman spectrum indicted that LEO interfered with the structure and biochemical compositions of biofilms. Moreover, it also impaired swimming motility, decreased hydrophobicity, inhibited auto-aggregation and reduced attachment to different food-contact surfaces. RT-qPCR revealed that LEO significantly downregulated transcription levels of biofilm-associated genes of V. parahaemolyticus. These findings demonstrate that LEO could be potentially developed as an antibiofilm strategy to control V. parahaemolyticus biofilms in food industries.